Development of PSAPS-TiO2 nanocomposite photocatalyst structure, mechanism, and application using response surface designs and molecular modeling - Nkwoada, Amarachi Udoka (Water science and technology : a journal of the International Association on Water Pollution Research, 2023)
Using periwinkle shell ash (PSA) and polystyrene (PS), a new-fangled PSAPS-TiO2 photocatalyst was fabricated. The morphological images of all the samples studied using a high-resolution transmission electron microscope (HR-TEM) showed a size distribution of 50-200 nm for all samples. The SEM-EDX showed that the membrane substrate of PS was well dispersed, confirming the presence of anatase/rutile phases of TiO2, and Ti and O2 were the major composites. Given the very rough surface morphology (atomic force microscopy (AFM)) due to PSA, the main crystal phases (XRD) of TiO2 (rutile and anatase), low bandgap (UVDRS), and beneficial functional groups (FTIR-ATR), the 2.5 wt.% of PSA@PS-TiO2 exhibited better photocatalytic efficiency for methyl orange degradation. The photocatalyst, pH, and initial concentration were investigated and the PSA@PS-TiO2 was reused for five cycles with the same efficiency. Regression modeling predicted 98% efficiency and computational modeling showed a nucleophilic initial attack initiated by a nitro group. Therefore, PSA@PS-TiO2 nanocomposite is an industrially promising photocatalyst for treating azo dyes, particularly, methyl orange from an aqueous solution